MRI-based parameters to assess the quality and prognosis of closed reduction in toddlers with developmental dysplasia of the hip - Cao, Jinchao; Li, Yu; Luo, Junzhong; Zheng, Zhaosu; Wang, Xuan; Su, Yunshan; Han, Jiuhui (Frontiers in Surgery, 2025)
BackgroundDevelopmental dysplasia of the hip (DDH) in toddlers (9–18 months) presents unique challenges due to incomplete ossification and anatomical complexity. Traditional imaging modalities, including x-ray, CT, arthrography, and ultrasonography, have limitations in assessing reduction quality. This study introduces a novel approach using only two magnetic resonance imaging (MRI) parameters-axial acetabular femoral head distance (aAFD) and coronal acetabular cartilage head index (CAHI)-to evaluate the quality of closed reduction (CR) and identify risk factors for redislocation.MethodsWe retrospectively reviewed 51 patients (58 hips) who underwent CR for DDH from June 2014 to June 2021. Pre- and post-CR pelvic radiographs assessed dysplasia grade, acetabular index (AI), and avascular necrosis (AVN). MRI, performed within three days post-CR, evaluated hip reduction quality using aAFD and CAHI. The reliability of these indices and their association with redislocation risk were analyzed.ResultsThe study cohort had a mean age of 13.7 ± 2.6 months and an average follow-up of 58.4 ± 13.5 months. CR was successful in 50 hips (86.2%), while 8 hips (13.8%) failed. Compared to failed cases, successful reductions showed significantly lower aAFD (2.4 ± 0.88 mm vs. 5.12 ± 1.70 mm, p < 0.05) and higher CAHI (83.4 ± 3.5% vs. 68.7 ± 4.9%, p < 0.05). AVN was observed in 10 hips (17.2%). Both aAFD and CAHI demonstrated strong intra- and interobserver reliability. ROC curve analysis showed excellent predictive accuracy for CAHI (AUC = 0.990) and aAFD (AUC = 0.968), with optimal thresholds aligning closely with the proposed cutoffs. Univariate analysis identified higher preoperative IHDI grade (p = 0.022) and more severe AVN (p < 0.01) as significant predictors of CR failure.ConclusionsClosed reduction with spica casting remains an effective treatment for DDH in toddlers. Postoperative MRI evaluation using only aAFD and CAHI offers a reliable and clinically applicable method for assessing reduction quality. Larger aAFD and lower CAHI values indicate a higher risk of reduction failure, making these indices valuable for postoperative assessment and decision-making.